Traditional Market Transformation Into Digital Market (Indonesian Traditional Market Research Library) - Hari Purwanto; Heny Sidanti; Dian Citaningtyas Ari Kadi (Publisher Cv. Inara, 2021)
For many centuries traditional markets have become the economic strength of Indonesian society where trading business actors gather to carry out buying and selling transactions. Along with the development of the era, the advancement of information technology is developing very rapidly and changing many patterns of people live from various aspects of life as well as trade. In conventional trade, relying on traditional markets is considered inefficient considering the too long distribution channels of goods and the emergence of additional costs in trade, which causes a high cost economy. The shift of traditional markets to digital markets is an inevitable demand. This study discusses Digital Transformation in traditional markets and how the process should take place to provide some solutions to existing problems. The method used in this research is library research. The research locations are traditional Indonesian markets. Sources of data in this study were collected by collecting methods through literature, scientific publications, information from the internet. The data is induced and concludes the arguments that are made. The findings of this study are: The digital transformation of traditional markets to digital markets has not been fully carried out in Indonesia. Solution: Traditional market players are starting to open up to the online market. It is time for the government to build online infrastructure to move traditional markets to digital markets, although not completely so that marketing efficiency and convenience can increase overall welfare.